The First Fleet Piano: Volume One and Two - Lancaster, Geoffrey (ANU Press, 2015)
During the late eighteenth century, a musical-cultural phenomenon swept the globe. The English square piano-invented in the early 1760s by an entrepreneurial German guitar maker in London-not only became an indispensable part of social life, but also inspired the creation of an expressive and scintillating repertoire. Square pianos reinforced music as life's counterpoint, and were played by royalty, by musicians of the highest calibre and by aspiring amateurs alike. On Sunday, 13 May 1787, a square piano departed from Portsmouth on board the Sirius, the flagship of the First Fleet, bound for Botany Bay. Who made the First Fleet piano, and when was it made? Who owned it? Who played it, and who listened? What music did the instrument sound out, and within what contexts was its voice heard? What became of the First Fleet piano after its arrival on antipodean soil, and who played a part in the instrument's subsequent history? Two extant instruments contend for the title 'First Fleet piano'; which of these made the epic journey to Botany Bay in 1787-88? The First Fleet Piano: A Musician's View answers these questions, and provides tantalising glimpses of social and cultural life both in Georgian England and in the early colony at Sydney Cove. The First Fleet piano is placed within the musical and social contexts for which it was created, and narratives of the individuals whose lives have been touched by the instrument are woven together into an account of the First Fleet piano's conjunction with the forces of history. Note: Volume 1 and 2 are sold as a set ($120 for both) and cannot be purchased separately.